Effect of processing techniques on new poly(ε‐caprolactone)‐embelin microparticles of biomedical interest. Issue 6 (16th March 2017) - Cortez Tornello, Pablo R.; Feresin, Gabriela E.; Tapia, Alejandro; Dzieciuch, Monika; Cuadrado, Teresita R.; Abraham, Gustavo A.
Abstract: Poly(ε‐caprolactone) microparticles containing embelin (PCLE) are prepared by electrohydrodynamic atomization (EHDA) and emulsion‐solvent evaporation techniques. Microparticles are characterized in terms of drug state, drug‐loading capacity, encapsulation efficiency, morphology and in vitro release in different mediums. Physicochemical, morphological, and thermal characterization is presented. Kinetic analysis is performed. EHDA microparticles present higher size, surface area, and encapsulation efficiency. The release profiles combine a high initial release, followed by a slow‐controlled release stage. Electrosprayed PCLE presented characteristics such as size (3.14 ± 0.05 μm), zeta potential (−49.22 ± 2.88 mV) and release profiles that could be attractive for the development of microcarriers for pulmonary administration of embelin.